Automatic Motion Control System of Roundness Testing Machine - Athiyyah Rieke Hisana; Arief, Dodi Sofyan (International Journal of Electrical, Energy and Power System Engineering, 2021)
Roundness has an important role in terms of dividing the load equally, determining component life, determining adjustment conditions, determining rotation accuracy, and facilitating lubrication. To measure the roundness required a tool that can perform measurements with precision. With a roundness measuring instrument that has an automatic motion control system it will be able to produce more efficient data retrieval and higher accuracy than previous research. The control system in this tool is a system that regulates the automatic movement of the roundness gauge. Where the function of this automatic motion control system is to measure the test object using a chuck as a clamp, the indicator dial is directed by the X and Y axes to the data collection point on the test object which is connected to the driving motor. Axis Y moves in translation to direct the indicator dial on the "arm" to the pick-up point which moves automatically depending on the selected data collection mode, then the indicator dial starts taking measurement data until the measurement data retrieval is complete, then the motor moves from top to bottom, to perform reversible data retrieval. Stepper motor on the chuck will also move. There are 2 mode in this machine, it is mode 1, where the resulting data is in the form of a "ring" and for mode 2, the resulting data is “spiral”. It was found that the translational speed of the screw shaft in the vertical movement is 0.025 m/s and the horizontal linear speed is 0.026 m/s.